2018
DOI: 10.1007/164_2018_183
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacosynthetic Deconstruction of Sleep-Wake Circuits in the Brain

Abstract: Over the past decade, basic sleep research investigating the circuitry controlling sleep and wakefulness has been boosted by pharmacosynthetic approaches, including chemogenetic techniques using designed receptors exclusively activated by designer drugs (DREADD). DREADD offers a series of tools that selectively control neuronal activity as a way to probe causal relationship between

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 221 publications
(382 reference statements)
0
7
0
Order By: Relevance
“…DREADD overexpression often occurs upon vector-mediated transgene delivery and could instigate receptor reserve, thereby avoiding receptor desensitization [ 3 ]. On the other hand, DREADD overexpression is also linked with constitutive activity of the receptor [ 71 , 72 ]. One study reported that DREADD overexpression perturbed endogenous GPCR signaling and alterations in both ion channel activity and intracellular signaling in the absence of the DREADD ligand [ 71 ].…”
Section: Dreaddful Hurdles In (Chronic) Chemogenetic Studiesmentioning
confidence: 99%
“…DREADD overexpression often occurs upon vector-mediated transgene delivery and could instigate receptor reserve, thereby avoiding receptor desensitization [ 3 ]. On the other hand, DREADD overexpression is also linked with constitutive activity of the receptor [ 71 , 72 ]. One study reported that DREADD overexpression perturbed endogenous GPCR signaling and alterations in both ion channel activity and intracellular signaling in the absence of the DREADD ligand [ 71 ].…”
Section: Dreaddful Hurdles In (Chronic) Chemogenetic Studiesmentioning
confidence: 99%
“…In so doing, anesthetics may rely on molecular targets with intrinsic temperature-sensing ability such as the K 2P channels or mitochondrial targets in critical cellular populations to inextricably link reductions in body temperature with decreased metabolism as occurs with endogenous sleep [111]. Anesthetic Actions on Endogenous Arousal-promoting Systems Neurons within the pedunculopontine and laterodorsal tegmentum (cholinergic), pontine reticular formation (unknown population), locus coeruleus (noradrenergic), parabrachial nucleus (glutamatergic), dorsal raphe (serotonergic), ventral tegmental area (dopaminergic), perifornical, lateral, and posterior hypothalamus (orexinergic), lateral hypothalamus (GABAergic) and tuberomammillary nucleus (histaminergic) are all capable of promoting the waking state [112]. Many of these nuclei have been explored as targets of the inhibitory effects of general anesthetics [113] (Figure 4).…”
Section: Reviewmentioning
confidence: 99%
“…Powerful new tools to interrogate sleep-wake regulating circuits have revealed new molecular and cellular markers, as well as novel network mechanisms and pathways that regulate wakefulness and sleep. While the ascending arousal system was first described as a reticular network of neurons projecting widely to the cortex and the spinal cord (Moruzzi and Magoun, 1949), it has become clear in the last few years that wakefulness and sleep are governed by distinct populations and subtypes of neurons (Varin and Bonnavion, 2018). Although specific, these neuronal systems are often redundant and reinforce each other.…”
Section: Prospects Of Pharmacogenetics For Personalized Sleep-wake Mementioning
confidence: 99%
“…These recent insights may necessitate an adaptation of the basic sleep-wake neurochemistry described above. They have been discussed in comprehensive reviews and other chapters of this book (Adamantidis and Luthi, 2018 ;Saper and Fuller, 2017;Tyree and de Lecea, 2017;Eban-Rothschild et al, 2018;Luppi and Fort, 2018;Varin and Bonnavion, 2018), and are not the focus of this chapter. In this article, firstly, genetic aspects of the current pharmacotherapy of sleep-wake disorders will be reviewed.…”
Section: Introductionmentioning
confidence: 99%